2017
DOI: 10.1371/journal.pone.0173574
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of intraocular lens subsurface nanoglistenings on functional visual acuity

Abstract: To investigate the influence of intraocular lens subsurface nanoglistenings (SSNGs) on functional visual acuity (FVA), thirty-nine eyes of 29 patients were examined in this study. The SSNG group comprised 19 eyes of 14 patients (75.7± 5.4 years, mean ± standard deviation), and the control group comprised 20 eyes of 15 patients (73.6 ± 6.5 years). The SSNGs were diagnosed on the basis of the typical whitish IOL appearance upon slit-lamp examination and results of densitometry regarding surface light scattering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…However, there could be further slight changes in visual function, which may not be detected with the conventional contrast sensitivity test. Such slight changes could be evaluated using a contrast visual acuity chart or functional visual acuity test 16 . Last, the ages of the three groups were different.…”
Section: Discussionmentioning
confidence: 99%
“…However, there could be further slight changes in visual function, which may not be detected with the conventional contrast sensitivity test. Such slight changes could be evaluated using a contrast visual acuity chart or functional visual acuity test 16 . Last, the ages of the three groups were different.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases glistening caused higher loss variance [ 26 ] or higher mean deviation [ 24 ] in the visual field, or impaired fundus visualization [ 27 ]. Examining differences in functional visual acuity, Hiraoka et al (2017) found that the visual maintenance ratio decreased, while the standard deviation of visual acuity increased in eyes with IOL subsurface nanoglistening [ 28 ]. Summarizing the data above, it seems that in most of the recent studies with sophisticated examination methods glistening was associated with some effect on visual function, although it was often only a moderate one.…”
Section: Discussionmentioning
confidence: 99%
“…However, some newer designs and materials used in IOLs have an increased tendency to form small, micrometer-sized, fluid-filled vacuoles within the bulk of the IOL [3–18]. These vacuoles, also commonly referred to as glistenings, have been shown to reduce contrast sensitivity (CS) and visual acuity (VA) [13, 14, 17, 1921], in some cases requiring IOL explantation [17, 21].…”
Section: Introductionmentioning
confidence: 99%
“…The grading scales generally range from grade 0, having no or trace vacuoles, to the highest grade, usually either 3 or 4, having extremely severe vacuoles. Various test methods have been employed to measure the clinical and nonclinical effects of vacuoles and light scatter in general, including subjective patient reports and VA tests [7, 10, 11, 13, 14, 16, 17, 1921], integrating spheres and transmission measurements [16, 21, 2426], C-Quant straylight meter measurements [18, 20, 2729], and in vivo slit-lamp and Scheimpflug tests and measurements [7, 10, 11, 1317, 1921, 23]. In addition, two different methods have been independently developed to physically scan around the back of the IOL to measure forward scattered light [26, 27, 30, 31].…”
Section: Introductionmentioning
confidence: 99%